2011
DOI: 10.4111/kju.2011.52.11.795
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneoscopic Partial Nephrectomy in a Horseshoe Kidney

Abstract: A 21-year-old woman with a 4 cm enhancing cystic renal mass in the left moiety of a horseshoe kidney was treated through a retroperitoneal laparoscopic approach. The tumor was excised completely with cold scissors, and renal parenchyma suturing with a surgical bolster was done with Vicryl 2-0 sutures. Choosing the proper approach according to the location of the lesion and the surgeon's experience with both approaches are of importance in laparoscopic surgery in horseshoe kidney cases. A preoperative kidney co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…To our knowledge, only four cases of laparoscopic nephron-sparing surgery for tumors in the horseshoe kidney have been published; two of them performed transperitoneally and the other two via a retroperitoneal approach. In this report, we describe the case of retroperitoneal laparoscopic partial nephrectomy for a solid renal mass in the left moiety of a horseshoe kidney 2, 3, 4, 5…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only four cases of laparoscopic nephron-sparing surgery for tumors in the horseshoe kidney have been published; two of them performed transperitoneally and the other two via a retroperitoneal approach. In this report, we describe the case of retroperitoneal laparoscopic partial nephrectomy for a solid renal mass in the left moiety of a horseshoe kidney 2, 3, 4, 5…”
Section: Introductionmentioning
confidence: 99%
“…Transperitoneal approach has been advocated for laparoscopic radical heminephrectomy and partial nephrectomy for malignant diseases in patients with HK (14,15,(18)(19)(20)(21)27). Conversely, Lee et al suggested retroperitoneal approach for laparoscopic partial nephrectomy in a HK for posterior and posterolateral lesions (26). In the current study, 7 (nonfunctional hydronephrotic and/or infected kidney = 6, kidney mass = 1) and 6 (nonfunctional kidney and/or infected kidney = 6) patients underwent transperitoneal and retroperitoneal laparoscopic heminephrectomy, respectively.…”
Section: Discussionmentioning
confidence: 69%
“…have suggested retroperitoneal approach for laparoscopic partial nephrectomy in a HK for posterior and posterolateral lesions. [ 9 ] Researches have reported transperitoneal as well as retroperitoneoscopic approaches for this, but transperitoneal route remains the popular one because of large working space and more familiarity with this approach.…”
Section: Discussionmentioning
confidence: 99%